Jebel Qatrani as Geotourism Sites in Egypt: An Exploratory Study - Maha Yehia Kamel Abdou; Suzan Bakri Hassan; Ghada Mohamed Wafik (Journal of Indonesian Tourism and Development Studies, 2020)
This research aims to identify the natural and geological features of Jebel Qatrani and to explore the role of geosite management in enhancing Jebel Qatrani as geotourism sites. A single case study was applied to reach the research aim. This research is based on a qualitative approach to obtain adequate information for achieving the research aim, direct observation was used for data collection. The results revealed that Jebel Qatrani has attractions such as fossils, rocks, mountains, and fossilized trees. The results indicated that Jebel Qatrani is characterized by unique diversity in geological and geomorphological. Jebel Qatrani has a history and geological importance. The results reported that there is a lack of marketing activities or promotion plans for promoting Jebel Qatrani. Also, there is no pamphlet and brochures to provide information to visitors. The results reported that there is a lack of signboard in place, and there is no food and beverage service. This research has several limitations. Firstly, this research focused on one case study of Jebel Qatrani. Â Secondly, the literature showed there had been a clear lack of prior research studies on geotourism sites in Egypt, in particularly Jebel Qatrani. Future research should address more geosites in Egypt; it also should undertake to test the findings of this research.Keywords: Attraction, Egypt, Geoheritage, Geosite, Geotourism, Management.